Multimodal Effects of Local Context on Target Detection: Evidence from P3b - Fogelson, Noa; Wang, Xue; Lewis, Jeffrey B; Kishiyama, Mark M; Ding, Mingzhou; Knight, Robert T (Journal of cognitive neuroscience, 2009)
We used the P300 component to investigate how changes in local context influenced the ability to detect target stimuli. Local context was defined as the occurrence of a short predictive series of stimuli before delivery of a target event. EEG was recorded in 12 subjects during auditory and visual sessions. Stimuli were presented in the center of the auditory and visual field and consisted of 15% targets (1000 Hz tone or downward facing triangle) and 85% of equal amounts of three types of standards (1500, 2000, and 2500 Hz tones or triangles facing left, upward, and right). Recording blocks consisted of targets preceded by either randomized sequences of standards or by sequences including a three-standard predictive sequence signaling the occurrence of a subsequent target event. Subjects pressed a button in response to targets. Peak target P300 (P3b) amplitude and latency were evaluated for targets after predictive and nonpredictive sequences using conventional averaging and a novel single-trial analysis procedure. Reaction times were shorter for predictable targets than for nonpredicted targets. P3b latency was shorter for predicted targets than for nonpredictive targets, and there were no significant P3b amplitude differences between predicted and random targets, as determined by both conventional averaging and single-trial analysis. Comparable effects on amplitude and latency were observed in both the auditory and visual modalities. The results indicate that local context has differential effects on P3b amplitude and latency, and exerts modality-independent effects on cognitive processing.